The side effects of national financial sector policies: framing the debate on financial protectionism - Roland Beck; John Beirne; Francesco Paternò; Jolanda Peeters; Julio Ramos-Tallada; Cyril Rebillard; Dennis Reinhardt; Lisa Weissenseel; Julia Wörz (European Central Bank (ECB), 2015)
The decrease of financial integration both at the global and European level reflects, to a certain extent, a market response to the crisis. It might, however, also be partly driven by policies such as capital flow management measures (CFMs). In addition, several other measures taken by central banks, regulators and governments in response to the crisis may have had less obvious negative side effects on financial integration. Against this backdrop, this paper explores broad definitions of financial protectionism in order to raise awareness of the fact that the range of policies which could negatively affect financial integration may be much wider than residency-based CFMs. At the same time, the paper acknowledges that these measures have mostly been taken for legitimate financial stability purposes and with no protectionist intentions. The paper considers five categories of policy measures which could contribute to financial fragmentation both at the global and at the EU level: currency-based measures directed towards banks, geographic ring fencing, some financial repression policies, crisis resolution policies with a national bias, and some financial sector taxes.
Keywords: F36; F42; F62; 330; capital controls; Financial integration; financial protectionism; macro-prudential policy